Product Analysis of Supercritical Fischer-Tropsch Synthesis: Utilizing a Unique On-Line and Off-Line Gas Chromatographs Setup in a Bench-Scale Reactor Unit - Amro Kasht (18806863) (2015)
The utilization of supercritical fluids (SCF) in the Fischer-Tropsch Synthesis (FTS) further complicates the hydrocarbon products identification and analysis process due to the dilution of hydrocarbon peaks by the predominant solvent peak. Therefore, in this project, a custom-made Gas Chromatography (GC) analysis system was designed and implemented to identify and quantify SCF-FTS products. The FTS products were identified using two different methods. The first was through retention time matching by injecting standard solutions, and the second was through the use of the GC/MS system. The quantification of CO and CH4 was achieved by using external standards, where the CO conversion was calculated by relating the peak area of CO to the peak area of an internal standard (argon) while the CH4 selectivity was calculated by relating the peak area of CH4 to that of CO. After setting and calibrating the GC system, two reaction conditions (gas phase: 240°C, 20 bar syngas with 2:1 H2:CO molar feed ratio and for the supercritical fluids FTS (SCF-FTS): 240°C, 65 bar with 20 bar syngas partial pressure and 2:1 H2:CO molar feed ratio) were used to compare the different FTS reaction media. The comparison between the gas phase FTS and the SCF-FTS showed the following: carbon monoxide conversion was improved by 14% in the SCF-FTS, while the hydrocarbon product profile SCF-FTS showed 78% reduction in light hydrocarbons (C1 - C4) products, 35% increase in middle distillates (C11 - C22) products compared to gas phase FTS. These improvements have resulted in higher chain growth probability for the SCF-FTS (α = 0.85) compared to the gas phase FTS (α = 0.76). These results are generally in agreement with previously reported enhancement in the SCF-FTS[1]. Other Information Published in: American Journal of Analytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.4236/ajac.2015.68064 Additional institutions affiliated with: Chemical Engineering Program - TAMUQ, Petroleum Engineering Program - TAMUQ